Does urban greenway design affect air pollution exposure? A case study of Seoul, South Korea. (September 2021) - Ahn, Haesung; Lee, Jeongwoo; Hong, Andy
Highlights: Ultrafine particles and black carbon concentrations were measured at different greenway designs. Pedestrian exposure to air pollution was lower on greenway than on sidewalk. Urban microenvironmental features, such as vegetation, could play a role. Vertical separation might be important for reducing air pollution exposure. Abstract: This study investigates whether different urban greenway designs can influence personal exposure to air pollutants in highly urbanized environments in Seoul, Korea. Mobile and in-situ measurements of ultrafine particles (UFP) and black carbon (BC) concentrations were conducted on three different types of urban greenway designs: 1) an at-grade greenway next to traffic; 2) an elevated greenway above (10−14 m) traffic; and 3) a sunken greenway below (2.5−3 m) traffic. Results from the mobile measurements showed that the UFP and BC concentrations were up to 30 % lower on all types of greenway than on sidewalks. This result was further confirmed by the in-situ measurement, which showed 47 % lower UFP concentrations in the sunken greenway and 80 % lower BC concentrations in the elevated greenway compared to the sidewalk. Pollutant concentrations also varied according to microenvironmental factors, such as land uses, height of surrounding buildings, nearby traffic, and vegetation. Our findings highlight the importance of considering air pollution exposure when designing urban greenways in highly urbanized environments. In particular, greenway designs that promote vertical separation from traffic sources might be crucial in mitigating air pollution exposure. The results of this study are based on data gathered over a six-day field measurement, and further studies over a longer time period are warranted to confirm our findings.